The use of short role-plays for an ethics intervention in university auditing courses - Taplin, Ross; Singh, A.; Kerr, R.; Lee, Alina (Routledge, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group This paper reports how short 10-minute role-plays can be used as an effective tool for ethics education within university auditing classes. A mixed method approach elicited student perceptions of role-plays in developing ethical awareness. While many students self-reported difficulty in recognising and dealing with the ethical dilemmas appropriately, most agreed role-plays helped them to prepare for dealing with these issues in the workplace. This was especially the case for students with English as an additional language. Students reported the role-play ethical dilemmas raised their awareness of the need to protect their professional independence. Students commented that they had a better understanding of the importance of the professional code of conduct and the code of ethics. Role-plays are a simple experiential learning approach that helps students to recognise ethical dilemmas, explore strategies to deal with such dilemmas in a safe environment, and practice listening and questioning skills to obtain information. Short role-plays can offer critical thinking opportunities that are more relevant to the student’s personal experience than case studies of historical ethical breaches.